Further observations from an experience of 660 cases of stereotactic tractotomy. Issue 578 (December 1973) - Knight, Geoffrey
Abstract : A study of the results of some 660 cases of stereotactic tractotomy shows that these have been consistent through a 12-year period, more than 50% of cases of resistant depression can be set free of medical care and another 25% at least can be improved. Comparable results are also obtained in obsessional illness and anxiety states, particularly those in which there is a depressive component. The original localization of the target site described in 1964 has not required modification but pathological studies and anatomical research has revealed new features concerning the anatomical connections affected by this operation. The lesion beneath the head of the caudate nucleus does not extend quite so far as the substantia innominata and should therefore be called subcaudate tractotomy. Connections from the anterior cingulate region and posterior orbital cortex are severed at this site but amygdalo-hypothalamic fibres are not interrupted directly, however; the projection from the amygdala to the dorsal median nucleus sends a radiation to the posterior orbital cortex which is divided here. In addition, important projections from frontal cortex to hypothalamus which bring the external milieu into association with the limbic system pass downwards through the target area beneath the head of the caudate nucleus and are also divided at this point, the localized lesion, therefore, produces a marked effect upon fibres which are concerned in emotional activity. The wellnigh specific effect in cases of depression raises the question whether the operation acts by modifying the intensity of emotional reactivity through limbic connections or has a more specific effect upon the cause of abnormal reactivity through fronto-hypothalamic connections exerting an influence on monoamine production in the hypothalamus.